2018
DOI: 10.1098/rsos.172368
|View full text |Cite
|
Sign up to set email alerts
|

Novel amphiphilic polyvinylpyrrolidone functionalized silicone particles as carrier for low-cost lipase immobilization

Abstract: The high catalytic activity, specificity and stability of immobilized lipase have been attracting great interest. How to reduce the cost of support materials has always been a hot topic in this field. Herein, for the development of low-cost immobilized lipase, we demonstrate an amphiphilic polyvinylpyrrolidone (PVP) grafted on silicone particle (SP) surface materials (SP-PVP) with a rational design based on interfacial activation and solution polymerization. Meanwhile, hydrophilic pristine SP and hydrophobic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Immobilization of CRL had caused decrease in the intensities of the XRD patterns as a result of CRL loading (Figure 3(c) and Figure 3(d)), which had led to decrease in the surface crystallinity. However, XRD patterns were found to remain as it was before the immobilization process, and this is in agreement with the finding by Zhang et al [44].…”
Section: Determination Of Cation Exchange Capacity (Cec)supporting
confidence: 92%
“…Immobilization of CRL had caused decrease in the intensities of the XRD patterns as a result of CRL loading (Figure 3(c) and Figure 3(d)), which had led to decrease in the surface crystallinity. However, XRD patterns were found to remain as it was before the immobilization process, and this is in agreement with the finding by Zhang et al [44].…”
Section: Determination Of Cation Exchange Capacity (Cec)supporting
confidence: 92%
“…The rational design is based on the interfacial activation and solution polymerization. The activity assay revealed that lipase immobilized with PVP functionalized silicone particles has exhibited higher catalysis activity and also better thermostability and reusability compared with hydrophilic pristine or hydrophobic polystyrene corded silicone particles [ 158 ]. Other examples include asparaginase, catalase, galactosidase, etc.…”
Section: Pharmaceutical and Other Applicationsmentioning
confidence: 99%
“…13 Immobilizing lipase on various carriers in different ways, can promise the function of improving the thermal stability and reusability, leading to lower cost of lipase application. 14,15 However, very few papers have described the enzymatic synthesis of lutein esters. Wang 16 and Hou 17 tried to catalyze the synthesis of lutein palmitate by Novozyme 435 and lipase-Pluronic F-127.…”
Section: Introductionmentioning
confidence: 99%